Local Wisdom of Mangrove Utilization in a Remote Coastal Village in Kubu Raya, West Kalimantan: An Ethnoscience Perspective for Contextual Science Education - Norma Eralita; Trida Ridho Fariz; Abdul Jabbar; Muhammad Ahganiya Naufal; Andhina Putri Heriyanti (Universitas Negeri Semarang, 2025)
Science education can be enriched by integrating local culture and wisdom, particularly through the exploration of mangrove ecosystems. Mangroves not only play an essential ecological role but also embody local knowledge that can be linked to scientific concepts. This study aims to identify and describe the local wisdom of the Nipah Panjang, Kubu Raya Regency, West Kalimantan community in utilizing various mangrove species as a source of contextual science learning. A descriptive qualitative design with an ethnopedagogical approach was employed, combining literature review, document analysis, and brief field observations. The findings reveal that six dominant mangrove species, Avicennia alba, Avicennia marina, Bruguiera gymnorrhiza, Excoecaria agallocha, Rhizophora apiculata, and Rhizophora mucronata, are utilized in diverse ways according to their biological traits and bioactive compounds. Their uses include construction materials, firewood, charcoal, traditional medicine (e.g., for eye treatment, anti-inflammatory purposes, and gastric remedies), and support for honeybee cultivation. Such practices highlight the integration of ethnoscientific knowledge with science concepts, including ecosystem adaptation, plant structure, wood properties, and bioactive compounds. By bridging modern science with local wisdom, science education can become more contextual and meaningful, while fostering environmental awareness and a conservation-oriented mindset toward coastal ecosystems.